ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK AIR MINERAL FROZEN DI PRIMA FRESHMART SEKOLAH VOKASI IPB - Doni Sahat Tua Manalu; Jelianus Nduru; Angelica Nabila Ahdy; Nadira Salwa Faizaty; Rhaka Agung Setiawan; Talitha Azalia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In Indonesia, bottled drinking water is the primary source of daily water consumption. The consumption of bottled drinking water in Bogor City is quite high 43.63%, while in Bogor Regency it is 30.43%. People usually used to like drinking mineral water from popular brands like Aqua and Amidis. Apart from that, sales of mineral water at Prima Freshmart have caught our attention despite selling many popular brands of mineral water. Brand Frozen mineral water is leading in sales at Prima Freshmart, indicating intense competition between the brands. The research aims to identify the attributes that influence consumer purchases of Frozen mineral water at Prima Freshmart. After comparing the attributes of Aqua, Frozen, and Amidis, three of the most popular bottled mineral water brands we determined which brand is superior. Using the Fishbein Multi-Attributes Behavior Methods, we have found that price, taste, and size are the most critical qualities that significantly influence consumer purchases. Our study concludes that Aqua brand mineral water is generally preferred over other brands.